Cyanoexosortase B is essential for motility, biofilm formation, and scytonemin production in a filamentous cyanobacterium - Gabriel A. Parrett; Daniel H. Haft; Maida Ruiz; Ferran Garcia-Pichel; Christopher C. Ebmeier; Douglas D. Risser (mSphere, 2025)
ABSTRACT Exosortases are involved in trafficking proteins containing PEP-CTERM domains to the exterior of gram-negative bacterial cells. The role of these proteins in cyanobacteria, where such homologs are common, has not been defined. The filamentous cyanobacterium Nostoc punctiforme contains a single putative exosortase, designated cyanoexosortase B (CrtB), implicated by previous work both in motility and in the production of the UV-absorbing pigment, scytonemin. To determine the role of crtB in N. punctiforme, a crtB-deletion strain (ΔcrtB) was generated. ΔcrtB presented the loss of motility, biofilm formation, and scytonemin production. In the case of motility, the ΔcrtB mutant exhibited a specific defect in the ability of hormogonia (specialized motile filaments) to adhere to hormogonium polysaccharide (HPS), and several PEP-CTERM proteins expressed in motile hormogonia were differentially abundant in the exoproteome of the wild-type compared with the ΔcrtB strain. These results are consistent with the hypothetical role of CrtB in the processing and export of PEP-CTERM proteins that play a critical role in stabilizing the interaction between the filament surface and HPS to facilitate motility and biofilm formation. In the case of scytonemin—the late biosynthetic steps of which occur in the periplasm and whose operon contains several putative PEP-CTERM proteins—ΔcrtB failed to produce it. Given the abundance of putative PEP-CTERM proteins encoded in the N. punctiforme genome and the fact that this study only associates a fraction of them with biological functions, it seems likely that CrtB may play an important role in other biological processes in cyanobacteria.IMPORTANCEIn gram-negative bacteria, exosortases facilitate the trafficking of proteins to the exterior of the cell where they have been implicated in stabilizing the association of extracellular polymeric substances (EPS) with the cell surface to facilitate biofilm formation and flocculation, but the role of exosortases in cyanobacteria has not been explored. Here, we characterize the role of cyanoexosortase B (CrtB) in the filamentous cyanobacterium Nostoc punctiforme, demonstrating that crtB is essential for motility, biofilm formation, and the production of the sunscreen pigment scytonemin. These findings have important implications for understanding motility and biofilm formation in filamentous cyanobacteria as well as efforts toward the heterologous production of scytonemin in non-native hosts.